Environmental impact by usage of pesticides in three melon producing areas in the Comarca Lagunera, México - Vargas-González, Gabriela (Universidad Autónoma de Tamaulipas, 2019)
The intensive use of highly toxic pesticides in the production of specialized fruit-horticultural crops entails environmental and social risks that can be measured through pesticide risk indicators to assess the potential negative impact of these products on ecosystems. In addition, this measurement enables the comparison of the achievements that result from the implementation of sustainable agricultural practices in terms of risk reduction due to the use of pesticides. The objective of this research was to estimate the potential environmental impact due to the use of pesticides in three melon production areas in the Comarca Lagunera. A cross-sectional descriptive study was carried out by applying a survey in 19 properties selected by non-probabilistic sampling. The Environmental Impact (EI) was evaluated using the Environmental Impact Quotient (EIQ) model, which is based on the calculation of the EIQ and the Environmental Impact Quotient in the Field (EIQF). Results show that the pesticides that contributed with the greatest environmental burden in the study areas were: Chlorothalonil (49 %), elemental sulfur (11 %) and endosulfan (10 %) in Mapimí; carbofuran (19 %), endosulfan (18 %) and carbendazim (12 %) in Matamoros-Viesca, and copper oxychloride (20 %), endosulfan (17 %) and mancozeb (17 %) in Tlahualilo. The production systems with the highest AI values were identified on intermediate (199 to 500) and late (201 to 701) sowing dates in Mapimí and late dates (132 to 383) in Matamoros-Viesca. The EIQ model allowed the identification of pesticides and production systems with the greatest negative environmental impact in the main areas of melon production in the Comarca Lagunera. Additionally, it provides a quantifiable scale that will allow the evaluation and comparison of future changes in the regional use of pesticides.